Heterotopic Heart Transplantation in Three Patients at the Texas Heart Institute - Frazier, O. Howard (1985)
Seventy-three orthotopic and three heterotopic transplantations have been done in our institution, and in this report, we describe the procedure and outcome of those who underwent heterotopic transplantation. Three patients were in critical condition while awaiting donors for heart transplantation, and in each case, a suitable donor could not be found. Smaller donor hearts became available, and knowing that these patients would die without some kind of immediate action, we performed heterotopic heart transplantations. Patient Number 1 was a 53-year-old diabetic man who was in the last stages of heart disease when a small donor heart became available. Because of his rapidly deteriorating condition, we did a heterotopic transplantation. The patient is presently well and functioning normally. Patient Number 2 was a 26-year-old woman who received the heart of a 13-year-old donor after it became obvious that she could not wait for a suitable donor. We performed a heterotopic transplantation, after which the patient continues to function well. Patient Number 3 was a 53-year-old man who weighed 260 lbs. When a suitable donor could not be found, the heart of a 170-lb man became available and was used in a heterotopic transplantation. This patient also continues to be active and well. After considering the various advantages and disadvantages of heterotopic transplantation, we are convinced that there is a definite place for this procedure in some patients with end-stage cardiac failure, although we still believe that orthotopic transplantation should be offered to most recipients.